PENGAWASAN KOMISI YUDISIAL TERHADAP HAKIM MAHKAMAH KONSTITUSI PERSPEKTIF FIQH SIYASAH - Safiudin, Achmad (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2016)
Abstract: The mechanism for supervision of Constitutional Court’s judges is conducted in two supervisory measures. They are internal supervision conducted by Supreme Court and external supervision by Judicial Commission. Although Judicial Commission is included as the member of internal integrity board of Constitutional Court judges, its supervision is limited for court session. This mechanism does not does not prevent the occurrence of misconduct because this ad hoc supervision board is only set up in case of alleged breach of ethical code by judge(s). In practice, Judicial Commission is not bestowed with sufficient authority to supervise the judges of Constitutional Court, since such role belongs only to ethical board in which the Judicial Commision is omitted from its membership. From the perspective of Islamic judicial law, this limited mechanism of supervision by Judicial Commission towards the judges of Constitutional Court is contradictory to Islamic judicial law. Islamic judicial law recognises Qâdhi al-Qudhâh that performs supervision with necessary authority. The external supervision of Judicial Commission should be given this authority to create a meaningful and effective supervision. Keywords: Islamic Judicial Law, judge supervision, Constitutional Court Abstrak: Mekanisme pengawasan hakim Mahkamah Konstutusi pasca putusan No.12/PUU-XII/214, dilakukan melalui dua jenis pengawasan yang diatur dalam UU No. 8 Tahun 2011, yaitu: Pertama, pengawasan internal yang dilakukan oleh Mahkamah Konstitusi. Kedua, pengawasan eksternal yang dilakukan oleh Komisi Yudisial. Meskipun Komisi Yudisial, dimasukkan dalam anggota Majelis Kehormatan Hakim Konstitusi (MKHK), tetapi pengawasan MKHK hanya sebatas dalam persidangan saja, mekanisme pengawasan Komisi Yudisial dalam MKHK tidak mencegah terjadinya penyimpangan, karena majelis ini baru dibentuk jika ada dugaan pelanggaran etika oleh hakim. Secara praktis, Komisi Yudisial tidak melakukan pengawasan secara leluasa, karena keleluasaan pengawasan hanya diberikan kepada Dewan Etik dan Komisi Yudisial tidak ikut andil dalam Dewan Etik. Dalam perspektif fiqh siyasah, mekanisme pengawasan Komisi Yudisial terhadap hakim Mahkamah Konstitusi yang kurang leluasa, kurang selaras dengan fiqh siyasah, karena dalam lembaga peradilan Islam, Qâdhi al-Qudhâh diberikan keleluasaan wewenang dalam mengawasi hal ihwal para qadhi oleh khalifah. Seharusnya pengawasan eksternal Komisi Yudisial diberikan keleluasaan wewenang dalam mengawasi hakim MK, supaya tercipta pengawasan yang efektif.